Using Graphic Organizers - Inspiration software to enhance EFL students’ writing self-efficacy - Chung Thi My Phung (Trường Đại học Trà Vinh, 2022)
Much research was carried out to indicate the difficulties that Vietnamese learners had to face when learning English skills. Some of them are about writing skill and writing ability. In this study, a quasi-experimental model was used to examine the effect of using graphic organizers in order to help learners enhance self-efficacy in writing essays, along with the Inspiration Software. This research was conducted in 30 second year students of the English major at Tra Vinh University (N = 30). The participants were divided into 2 groups. One group was trained with traditional instruction called control group, while the experimental group was approached with graphic organizers as a new method to learn writing skills. Both of pre-test and post-test were used to determine the changes in participants' perceived writing self-efficacy. The finding shows that the positive effects of using graphic organizers may help students enhance writing self-efficacy.